The king's speech - Firth, Colin, 1960-; Rush, Geoffrey, 1951-; Bonham Carter, Helena, 1966-; Pearce, Guy, 1967-; Spall, Timothy, 1957-; Jacobi, Derek; Ehle, Jennifer, 1969-; Andrews, Anthony, 1948-; Bloom, Claire, 1931-; Best, Eve, 1971-; Gambon, Michael; Canning, Iain.; et al. ([United States] : Weinstein Company Home Entertainment ; Beverly Hills, CA : distributed by Anchor Bay Entertainment, 2011)
The story of King George VI of Britain, his impromptu ascension to the throne and the speech therapist who helped the unsure monarch become worthy of it.
Originally released as a motion picture in 2010.
Special features: Featured commentary with director Tom Hooper ; The king's speech: and inspirational story of an unlikely friendship ; Q & A with the director and cast ; Speeches from the real King George VI ; The real Lionel Logue ; The Stuttering Foundation (Public service announcement)
Editor, Tariq Anwar ; music, Alexandre Desplat ; director of photography, Danny Cohen.
Colin Firth, Geoffrey Rush, Helena Bonham Carter, Guy Pearce, Timothy Spall, Derek Jacobi, Jennifer Ehle, Anthony Andrews, Clair Bloom, Eve Best, Michael Gambon.
MPAA rating: R; for some language.
DVD, anamorphic widescreen 1.78:1, NTSC; region 1; Dolby Digital 5.1.
Keywords: George -- VI, -- King of Great Britain, -- 1895-1952 -- Drama; Logue, Lionel, -- 1880-1953 -- Drama; Speech therapists -- Australia -- Drama; Speech therapy -- Great Britain -- Drama; Speech disorders -- Patients -- Drama; Biographical films; Historical films; Feature films; Fiction films; Feature films -- Great Britain; Feature films -- Australia; Feature films -- United States; Biographical films -- Great Britain; Historical films -- Great Britain; Motion pictures -- Great Britain; Foreign films; Video recordings for the hearing impaired